TOTAL THORACOSCOPIC THORACIC LYMPHADENECTOMY IN THE TREATMENT OF ESOPHAGEAL CANCER - Barros, Inês; Bártolo, Joana; Romano, Joana; Ramos, Paulo; Monteiro, Cecília; Casaca, Rui; Abecasis, Nuno (Revista Portuguesa de Cirurgia, 2022)
INTRODUCTION:  In esophageal cancer, surgical resection and its corresponding lymphadenectomy remains the only therapeutic strategy that offers a possibility of cure. Despite the fact that a minimally invasive approach allows for an adequate lymphadenectomy with less associated morbidity, its high technical complexity means that many centers still do not perform it routinely. OBJECTIVE:  Systematization of the appropriate surgical technique for the performance of thoracoscopic thoracic lymphadenectomies in the treatment of esophageal cancer. This video shows, in a systematic way, a total thoracic lymphadenectomy, performed by thoracoscopy in a high-volume center (40 esophagectomies/year), highlighting the anatomy and its critical steps, in order to allow for an execution with low morbidity rates. VIDEO :  https://youtu.be/dEpM2on0dto